Collaboration between Guidance and Religious Education Teachers in Building Islamic Character Through the Character Building Program at MTS-Islamiyah Cianjur - Uus Husni Hoer; Delima Damiati; Paska Florensa; Fitri Wulandari (Pasundan Social Science Development, 2026)
The problem of students' Islamic character remains a challenge in education, especially in the era of globalization influenced by social media and the weakening role of the family environment. At MTs Islamiyah Cianjur, various problems were found, such as student truancy, lying, brawls, and declining manners and speech. To address this, the school developed a character-building program with a focus on collaboration between Guidance and Counseling (BK) and Islamic Religious Education (PAI) teachers. This study used a descriptive qualitative method with a case study approach. The results showed that BK teachers not only carry out administrative duties but also play a role in developing students' moral and spiritual development. Meanwhile, Islamic Religious Education (PAI) teachers act as spiritual educators, fostering awareness of Islamic values ??in a personal and contextual manner. The collaboration between the two, built on open and complementary communication, has proven effective in shaping students' Islamic character.